The Influence of Knowledge Level, Perception, and Religiosity among Working Women in Semarang City on Halal Cosmetics Use - Primahana, Sheilanita Aulia; Rosyid, Abdur; Dewi, Rissa Maharani; Febrinasari, Nisa; Januarti, Ika Buana; Sabiti, Farroh Bintang (Halal Science, 2026)
This study examined the associations of knowledge level, perception, and religiosity with halal cosmetics use among working women in Semarang City. A quantitative cross-sectional design was used, involving 111 respondents selected via snowball sampling. Data collected through a structured online questionnaire were analyzed using multiple linear regression. Results showed that knowledge (β = 0.070), perception (β = 0.077), and religiosity (β = 0.034) significantly and positively influenced halal cosmetics use (all p < 0.05), with perception emerging as the strongest predictor. The model explained a substantial proportion of variance (R^2 = 0.469). Respondents with positive perceptions were more likely to use halal-certified cosmetics consistently, indicating that usage is driven not only by religious values and knowledge but also by practical factors like accessibility, quality, safety, and consumer confidence. Although the cross-sectional design and non-probability sampling may limit generalizability, these findings offer valuable insights. Future studies should involve larger, more geographically diverse populations and explore additional marketing variables. Ultimately, these insights can guide cosmetic manufacturers, certification authorities, and policymakers in developing targeted educational strategies, transparent communication, and consumer-oriented promotional approaches within Indonesia’s competitive urban halal personal care market.